Particle motion around open mixing screws: optimal screw angular velocity. Issue 3 (3rd May 2016) - Keppler, Istvan; Varga, Attila; Szabo, Istvan; Katai, Laszlo; Fenyvesi, Laszlo
Abstract : Purpose: – The purpose of this paper is to analyze the effect of screw angular velocity on the mixing efficiency of open mixing screws. Design/methodology/approach: – Measurements and discrete element method (DEM)-based simulations. Findings: – There is an optimal screw rotation angular velocity above which there is no reason to operate the mixing apparatus, as the mixing efficiency does not increase with the increase of screw angular velocity. Research limitations/implications: – By using DEM-based optimization of open mixing screw apparatus, the effective mixing of agricultural grains can be achieved. The quality degradation of the dried product can be reduced. Practical implications: – The causeless increase of screw angular velocity results higher power consumption and quality degradation because of the increasing value of contact forces arising between the mixed particles. Originality/value: – The paper shows that by using discrete element-based simulations, the optimal working parameters of open mixing screws can be evaluated.